EKSISTENSI CIVICS SEBAGAI FONDASI AWAL PENDIDIKAN KEWARGANEGARAAN DI INDONESIA - Fitri Hariani Harahap; Hendra Rahayu, Melva Adelia Manurung; Paskaria Simbolon, Reh Bungana Beru Perangin-Angin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The existence of Civics as the initial foundation of Citizenship Education (PKN) in Indonesia has played a crucial role in shaping character and national awareness since the early days of independence. Civics became the forerunner to the birth of PKN, which aims to instill moral values, nationalism, and civic responsibility in a democratic state life. This study aims to describe the history of Civics as the first generation of PKN in Indonesia and analyze the basic values ​​of Civics that are still relevant and embedded in current civic education. This study uses a descriptive qualitative method with research subjects consisting of PPKn teachers, BK teachers, and students. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis included the stages of data collection, reduction, presentation, and drawing conclusions. Data validity was tested using credibility, transferability, dependability, and confirmability tests. The results of the study indicate that Civics has a significant contribution to the development of civic values ​​in Indonesia, especially religious values, morals, justice, responsibility, democracy, and tolerance, which are the basis for the formation of citizens with character and a nationalist spirit.